Sensorimotor correlates of sit-to-stand in healthy adults - McDonald, Caitlin; Villarejo Mayor, John Jairo; Lennon, Olive (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionStanding up, while one of the most common daily activities is also one of the most mechanically demanding tasks undertaken in daily life. Mobility impairments, in particular neurological conditions, often impede individuals’ ability to stand up independently. Despite the obvious association between neurological disorders and impairment of sit-to-stand, the neurophysiological basis of this functional movement is not well understood, particularly at brain level.MethodsSubjects (N = 20, 4 males) performed fifteen sets of five sit-to-stand transitions on an armless, backless seat adjusted to the knee joint height of each participant. Electromyography (EMG) was recorded from the bilateral vastus lateralis, biceps femoris, tibialis anterior, and gastrocnemius. Surface electroencephalography (EEG) activity was recorded using eight focused bipolar channels over the sensorimotor cortex. Kinematic data was recorded using a three-dimensional motion capture camera system.ResultsEMG and kinematic data confirm distinct flexion and extension phases of the movement with timed co-activation of the quadriceps and hamstrings, and gastrocnemius and tibialis anterior. EEG data demonstrates a change in cortical activity across the phases of sit-to-stand, notably event-related desynchronisation in the higher band frequencies (14–35 Hz) in the flexion and early extension phase, most prominent at the central Cz electrode. Corticomuscular coherence was observed during the flexion and extension phases between the Cz electrode and the biceps femoris and gastrocnemius, in a subgroup of participants.DiscussionThis study provides insights into how cortical activity modulates movement execution during sit-to-stand. The event-related spectral perturbation data contributes to our understanding of this movement by revealing frequency specific changes in cortical activity across the phases of the sit-to-stand transition. Corticomuscular coherence was highest during the flexion phase when transitioning to extension, congruent with electroencephalography and Electromyography activity levels. Whether the brain activity observed is sufficient to distinguish between kinematic phases remains to be determined.